Zeichnung. - O.Ö. Landesmuseum, Linz (Linz : O.Ö. Landesmuseum, 1986)
Blaas, Franz ; Böhm, Wolfgang ; Damisch, Gunter ; Jascha, Johann ; Klopf, Karl-Heinz ; Riedl, Alois ; Schleinkofer, Karl ; Ströhle, Karl-Heinz ; Zechyr, Otmar
Zeichnung, Landesgalerie am O.Ö. Landesmuseum, Linz, 22.5. - 22.6.1986
boek